Association of Canine Osteosarcoma and Monocyte Phenotype and Chemotactic Function. (23rd June 2016) - Tuohy, J.L.; Lascelles, B.D.X.; Griffith, E.H.; Fogle, J.E.
Abstract : Background: Monocytes/macrophages are likely key cells in immune modulation in dogs with osteosarcoma (OSA). Increased peripheral monocyte counts are negatively correlated with shorter disease‐free intervals in dogs with OSA. Understanding the monocyte/macrophage's modulatory role in dogs with OSA can direct further studies in immunotherapy development for OSA. Hypothesis/Objectives: That OSA evades the immune response by down‐regulating monocyte chemokine receptor expression and migratory function, and suppresses host immune responses. Animals: Eighteen dogs with OSA that have not received definitive treatment and 14 healthy age‐matched controls Methods: Clinical study—expression of peripheral blood monocyte cell surface receptors, monocyte mRNA expression and cytokine secretion, monocyte chemotaxis, and survival were compared between clinical dogs with OSA and healthy control dogs. Results: Cell surface expression of multiple chemokine receptors is significantly down‐regulated in peripheral blood monocytes of dogs with OSA. The percentage expression of CCR2 (median 58%, range 2–94%) and CXCR2 expression (median 54%, range 2–92%) was higher in control dogs compared to dogs with OSA (CCR2 median 29%, range 3–45%, P = 0.0006; CXCR2 median 23%, range 0.2–52%, P = 0.0007). Prostaglandin E2 (PGE2 ) (OSA, median 347.36 pg/mL, range 103.4–1268.5; control, 136.23 pg/mL, range 69.93–542.6, P = .04) and tumor necrosis factor‐alpha (TNF‐α) ( P = .02) levels are increased in OSA monocyte culture supernatants compared to controls. Peripheral blood monocytes of dogs with OSA exhibit decreased chemotactic function when compared to control dogs (OSA, median 1.2 directed to random migration, range 0.8–1.25; control, 1.6, range of 0.9–1.8, P = .018). Conclusions and Clinical Importance: Dogs with OSA have decreased monocyte chemokine receptor expression and monocyte chemotaxis, potential mechanisms by which OSA might evade the immune response. Reversal of monocyte dysfunction using immunotherapy could improve survival in dogs with OSA.